Toward a first-principles description of transverse momentum dependent Drell-Yan production in proton-nucleus collisions - Weiyao Ke; John Terry; Ivan Vitev (Journal of High Energy Physics)
Abstract We study Drell-Yan production in proton-nucleus reactions in the limit of small transverse momentum, emphasizing the role of the cold nuclear matter effects. The TMD distributions that enter the factorized cross section could differ from the ones on free nucleons due to intrinsic changes in the non-perturbative nucleon and nuclear structure. Here, we focus instead on the perturbative dynamics, shown to arise from forward scattering between the parton constituents of the proton and the nuclear medium. The new contributions to the TMD Drell-Yan cross section are derived up to next-to-leading order in the strong coupling constant, and to the first order in the medium opacity. We demonstrate that the collinear and rapidity divergences related to parton showers in the nucleus and the coherent nature of radiation due to Landau-Pomeranchuk-Migdal effect lead to i) an in-medium renormalization group equation that encodes the transverse momentum dependence of parton energy loss, and ii) a Balitsky-Fadin-Kuraev-Lipatov evolution equation with a restricted phase space for the forward scattering cross section. The relation of our results to the phenomenological extraction of nuclear TMDs is discussed and the new formalism is applied to Drell-Yan production at small transverse momentum in p+A reactions.